Real-time detection of root zone-CO2 and its potential for irrigation scheduling - Klaus Spohrer (2018)
© 2015 by the authors. The suitability of root zone-CO < inf > 2 < /inf > measurements (WR-CO < inf > 2 < /inf > ) for irrigation scheduling was investigated and evaluated. The basic assumption was that plants reduce root respiration as a reaction to water deficit. A study with apple trees proved that measured WR-CO < inf > 2 < /inf > originates in large parts (56-72 %) from plant specific CO < inf > 2 < /inf > production (mainly root respiration). Furthermore, WR-CO < inf > 2 < /inf > reacts to irrigation as well as correlates with soil water content. Since WR-CO < inf > 2 < /inf > variations were also reflected in changes of plant water status, basic potential of WR-CO < inf > 2 < /inf > for irrigation demand assessment of the investigated apple trees is apparent. The transferability to other crops will be investigated.